The Impact of Organic Biofertilizer Application in Dairy Cattle Manure on the Chemical Properties of the Soil and the Growth and Nutritional Status of Urochroa Grass - Soares Filho, C. V. [UNESP]; Cavazzana, J. F. [UNESP]; Heinrichs, R. [UNESP]; Vendramini, J. M. B.; Lima, G. C. [UNESP]; Moreira, A. (Taylor & Francis Inc, 2018)
The management of nitrogen (N) fertilization in pasture has great importance for yield and maintenance of Brazilian livestock. The objective of this study was to evaluate soil chemical attributes, shoot dry weight yield (SDWY) and roots dry weight yield (RDWY), nutritional status and nutritive value of Mulato II Urochloa grass that received organic biofertilizer rates as N source. The treatments were arranged in completely randomized blocks, were fertilized with six organic biofertilizer rates (0, 25, 50, 100, 200, and 400 m(3) ha(-1)) and five replicates during four harvest cycles. There was a quadratic response in the accumulated SDWY for up to a rate of 400 m(3) ha(-1) and RDWY with 330 m(3) ha(-1) of organic biofertilizer. The organic biofertilizer influenced the soil chemical attributes and foliar nutrient concentration. However, only the crude protein content presented a quadratic response, and neutral detergent fiber and acid detergent fiber levels were not affected by the influence of organic biofertilizer applied to the soil.
Keywords: Cattle manure; crude protein; nutritional status; roots yield; shoot dry weigh yield